Preliminary experiments on potential use of salt-water battery 4 for cheap electric storage: Work in progress - Yunita Umniyati; Kevin Indra Wijaya; Ericson Sinaga; Victor Christianto (Universitas Padjadjaran, 2021)
The effective use of electricity from renewable sources requires large-scale stationary electrical energy storage (EES) systems with rechargeable high-energy-density, cheap batteries. While batteries using lithium, cadmium, lead-acid etc. have been widely used, there is an alternative source i.e. salt-water which is quite abundant in nature and known as electrolyte. We report a series of preliminary experiments on potential use of salt-water as cheap source of renewable battery with various kind of metals as anode and cathode. The purpose of these experiments is to find out which combination of anode and cathode is capable to generate the best performance in terms of electric voltage. It is hoped that these experiments will lead to practical implementation in the near future.